2022
DOI: 10.1097/cce.0000000000000758
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Oximetry and Race in Critically Ill Adults

Abstract: For critically ill adults, oxygen saturation is continuously monitored using pulse oximetry (Spo 2 ) as a surrogate for arterial oxygen saturation (Sao 2 ). Skin pigmentation may affect accuracy of Spo 2 by introducing error from statistical bias, variance, or both. We evaluated relationships between race, Spo 2 , Sao 2 , and hypoxemia (Sao 2 < 88%) or hyperoxemia (Pao 2 > 150 mm Hg) among adults receiving mechanical ventilation in a medical ICU. DESIGN:Single-center, observational study. SETTING: Medical ICU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…First, we hypothesized that inaccuracies in pulse oximetry contributed at least partially to the racial differences in predictive performance of the XGB model, given that pulse oximetry has been consistently shown to be less accurate in Black patients (16)(17)(18), and even the ROX index also had slightly worse performance in Black patients (although not statistically significant). However, removing pulse oximetry variables from the XGB model did not reduce the racial bias, suggesting that potential inaccuracies in pulse oximetry or vital signs did not completely account for the discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…First, we hypothesized that inaccuracies in pulse oximetry contributed at least partially to the racial differences in predictive performance of the XGB model, given that pulse oximetry has been consistently shown to be less accurate in Black patients (16)(17)(18), and even the ROX index also had slightly worse performance in Black patients (although not statistically significant). However, removing pulse oximetry variables from the XGB model did not reduce the racial bias, suggesting that potential inaccuracies in pulse oximetry or vital signs did not completely account for the discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…Polfer et al (28) found that Black patients with limb ischemia were significantly less commonly identified compared with White patients (23.3% vs. 92.9%). Conventional pulse oximetry is also less sensitive to hypoxemia in Black individuals (29–32). Neoplastic CCC was more common in the White cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Racial Differences in Pulse Oximetry. Recent studies in both adult and pediatric patients have demonstrated that pulse oximeters overestimate the true arterial oxygen saturation in non-White patients (18,19). Given our use of OSI in this study, we conducted a sensitivity analysis.…”
Section: Batch Correctionmentioning
confidence: 99%